Comparative antiseizure medications of adjunctive treatment for children with drug-resistant focal-onset seizures: A systematic review and network meta-analysis - Zhang, Lanlan; Li, Yuehong; Wang, Weikai; Wang, Chengzhong (Frontiers in Pharmacology, 2022)
Purpose: In this study, we intended to compare and rank the efficacy and acceptability of antiseizure medications (ASMs) for adjunctive treatment of children with drug-resistant focal-onset seizures. Method: We conducted a computerized search of PubMed, EMBASE, Cochrane Library, Web of Science, and Google Scholar to identify eligible randomized controlled trials (RCTs) published before 31 May 2022. We included studies evaluating the efficacy and tolerability of antiseizure medications for children with drug-resistant focal-onset seizures. The efficacy and safety were reported in terms of responder and dropout rate along with serious adverse events, the outcomes were ranked with the surface under the cumulative ranking curve (SUCRA). Results: A total of 14 studies (16 trials) with 2,464 patients were included, involving 10 active antiseizure medications. For the primary endpoint of at least 50% reduction in focal-onset seizures, the surface under the cumulative ranking curve ranking suggested that lamotrigine and levetiracetam were more effective as compared with other antiseizure medications; moreover, levetiracetam had the highest probability of rank first for achieving seizure freedom. Concerning tolerability, oxcarbazepine and eslicarbazepine acetate were associated with higher dropout rates relative to other antiseizure medications and placebo, and topiramate was associated with higher occurrence of side effects. No significant differences were found between active antiseizure medications concerning dropout for side effects. Conclusion: According to the surface under the cumulative ranking curve ranking, lamotrigine, levetiracetam, and oxcarbazepine were more efficacious than other active antiseizure medications in terms of responder rate. Concerning tolerability, oxcarbazepine was more likely to lead to dropout and topiramate was associated with higher occurrence of side effects.